Histopathological Evaluation of the Teratogenic Effects of Lixisenatide on the Cerebral Cortex of Developing Chick Embryo - Srivastava, Amit Kumar; Yadav, Yogesh; Yadav, Swati; Bhardwaj, Harshita; Gupta, Ashok Kumar (Innovations in Biological Science Vol. 9, 2024)
Background and Objectives: Chick embryos are commonly used in research to investigate the negative impacts of various drugs. The drug lixisenatide is superior to other GLP1 receptor agonists for treating type 2 diabetes mellitus. It is recommended to take 20 µg of lixisenatide daily for type 2 diabetes mellitus. However, there are no clear human dose recommendations based on age and weight. It is important to conduct further research on the teratogenic effects of lixisenatide to determine the potential toxicity of the drug for human welfare. Materials and Methods: It’s an experimental study conducted at the Department of Anatomy, Santosh Medical College, Ghaziabad, Uttar Pradesh. The study aimed to investigate the effects of specific parameters in two groups, a control group, and an experimental group. The expected mean ± SD of the parameter for the control and experimental groups were found to be 27±5.32 and 32±5.30, respectively, based on a literature survey and pilot study. To achieve an appropriate sample size, G*Power software was used, with an alpha level of 5% and a power of 95.36%, which resulted in an effect size of 1.961 and a sample size of 28 for each group experimental and control (A, AC, B, BC, C, CC, D, DC, E, EC), leading to a total sample size of 280. The chick embryos were first sacrificed and then dissected, and the brain was separated and kept in a 10% formaldehyde solution. To identify histological characteristics of the cerebral cortex, tissue was sectioned and stained with H & E stain then observed by the light and compound microscope were used for sections. Results: During the experiment, Lixisenatide induced necrotic changes and cellular condensation in the chick embryo’s cerebral cortex, specifically in groups C, D, and E. Additionally, there was mild distortion found in the cortex indicating degenerative changes in experimental group E. There was a statistically significant increase in histopathological changes observed in the cerebral cortex as the dose of Lixisenatide increased in each experimental group (p<0.05). Conclusion: Insufficient research has been conducted on the development of side effects of lixisenatide. Despite its widespread use, observations have revealed that lixisenatide has adverse effects on the cerebral cortex of chick embryos, including cellular condensation and necrotic changes, and mild distortion found in the cortex indicating degenerative changes in experimental groups C, D, and E. Therefore, it is imperative that the administration of this vital medication is carefully considered to prevent neuronal complications. Further research is necessary to fully understand the potential adverse effects of lixisenatide on brain development.